Meningkatkan Daya Saing Dan Daya Jual Produk Dengan “Strategi Pemasaran” Sederhana - Nur Cahyadi; Putra Panji Respati; Abi Hanif Dzulquarnain (ALKHIDMAH: Jurnal Pengabdian dan Kemitraan Masyarakat, 2023)
Viewing is currently very popular with many people to earn income or as a side job for some people, so many people start by creating new products or innovative products, these products are marketed in various ways and use various strategies. The aim of this service is to provide knowledge and understanding to the public so that when marketing their products they have a simple strategy so that their goods or products can be accepted by consumers. This activity is carried out using an outreach method to people who have goods or products who do not yet know the strategy for marketing their products. The marketing strategy has several ways or methods that can make sales easier. The definition of marketing is a comprehensive, integrated and planned activity carried out by an organization or institution in carrying out business in order to be able to accommodate market demand by creating products with selling value, determining prices, communicating, delivering and exchanging offers that are of value to consumers. clients, partners and the general public. And society is able to increase its competitiveness, if we use products that are already widely used by other people, the competitiveness of our products is higher and the selling power of the product is greater because many people are selling it and it is included in the needs that consumers want.